Advancing trait-based biomonitoring approach for freshwater ecosystems assessment in Africa: current status, challenges, and future directions - Edegbene, Augustine Ovie; El Yaagoubi, Sara; Mohammed, Yakubu Manbe; Harrak, Rihab; Edegbene Ovie, Tega Treasure; Azmizem, Ahlame; Errochdi, Sanae; Olatunji, Olusegun Emmanuel; Keke, Unique Ndubuisi; Sankoh, Abdul Aziz; Abubakar, Muhammad Danjuma; Irefo, Anagha Linus; et al. (Frontiers in Environmental Science, 2025)
Freshwater ecosystems across Africa are increasingly threatened by anthropogenic pressures, including land-use changes, pollution, hydrological alterations, and climate variability. While traditional taxonomic approaches for biomonitoring these ecosystems remain valuable, they often fall short in detecting ecological processes and stressor-specific responses. In contrast, trait-based approaches (TBAs) provide a function-oriented perspective on ecosystem integrity by linking organismal traits to environmental gradients. This review synthesizes the current state of TBAs in African freshwater ecosystems assessments, highlighting their limited but growing application across the continent. We identify key challenges hindering wider implementation, such as the scarcity of trait databases tailored to African taxa, inconsistent taxonomic resolution, limited institutional capacity, and gaps in ecological traits knowledge. Despite these limitations, TBAs offer strong potential to improve diagnostic precision, enable ecological comparisons across regions, and support resilience assessment in data-limited contexts. We suggest future avenues to advance standardized trait frameworks, regional trait banks, and coordinated monitoring schemes in line with global biodiversity objectives and sustainable freshwater ecosystems management in Africa.